Perlindungan Hukum terhadap Produk Makanan KUALAT (Kulit Ayam Lada Nikmat) sebagai Potensi Indikasi Geografis Khas Kabupaten Karawang - Warohmah, Sipa Mawadah; Ananda, Via Rizky; Adelia, Farah; Habib, Farhan Abdurrahman; Mustofa, Dion; Saripudin, Asep (Jurnal Ilmiah Wahana Pendidikan, 2024)
Intellectual Property Rights (IPR) can be defined as the right to obtain legal protection for intellectual property in accordance with IPR laws and regulations such as the Copyright Act, Patents, Industrial Designs, Trade Secrets, and Trademarks. IPR has an important role in economic development and trade. Through a trademark a business actor can maintain and provide assurance of the quality of goods and / or services produced. Indonesia is a country that has enormous potential for Intellectual Property Rights (IPR), especially those related to Geographical Indications. Many Geographical Indication products exist in Indonesia, one of which is KUALAT. KUALAT is a typical karawang food product made from chicken skin that is fried until crispy. Indonesia adheres to one of the principles that the legal protection of a trademark will only be given to the party who first applied for registration of the trademark. Where the typical kualat product of Karawang has been successfully registered at the Directorate General of Intellectual Property (DJKI) of the Ministry of Law and Human Rights with registration number IDM001060934, therefore with the legality of the registration number for the registered kualat product brand, this product has had protection for its brand products.